A Low-Cost Microcontroller Implementation of Fuzzy Controller for Renewable Energy Converters - Saba Javed; Kashif Ishaque; Jonathan Shek; Saqib Jamshed Rind (International Transactions on Electrical Energy Systems)
Microcontrollers (μCs) are extremely useful in renewable energy (RE) converters, where numerous onboard control actions need to be executed at low cost. This paper focusses on a cost-effective implementation of a fuzzy controller (FC) for the regulation of converters that are normally employed in RE applications such as solar, wind, and tidal. The μC realization has been achieved through simplification of a dual-input FC (DFC) into a single-input FC (SFC) using the signed distance approach, followed by the piece-wise linear (PWL) simplification of SFC named as piece-wise-linear single input FC (PWL-SFC). Despite the elimination of the fuzzification, knowledge inference, and defuzzification stages, PWL-SFC exhibits a similar control performance to that of DFC. The proposed PWL-SFC is tested through modeling and simulation using the MATLAB Simulink platform and experimentally validated through a low-cost dsPIC μC. The results reveal that the proposed PWL-SFC requires negligible tuning effort and uses three orders of magnitude less computational power compared to DFC.